2022
DOI: 10.3390/su14116461
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Analysis of a Municipal Wastewater Treatment Plant through Emergy Evaluation

Abstract: Water and wastewater treatment plants are essential for the supply of drinking water for consumption and the treatment of effluents produced by human/industrial activities. However, few studies deal with the investments and sustainability of these services, which consider both the contribution of nature and society. This study uses the emergy approach to evaluate a wastewater treatment plant located in the northeastern part of Romania, in Iași city. An assessment of the environmental costs of natural fluxes re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…It is observed that 8 of the 10 most cited documents correspond to the period before 2010 and only two were published after 2015. Research reports emergy analysis in different scenarios: constructed wetlands (Arias and Brown, 2009;Chen et al, 2009;Siracusa and la Rosa, 2006;Zhou et al, 2009), municipal wastewater (Björklund et al, 2001;Ciobanu et al, 2022), organization system (Bastianoni and Marchettini, 1997) and specifically water treatment with microalgae (Grönlund et al, 2004).…”
Section: Documentsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is observed that 8 of the 10 most cited documents correspond to the period before 2010 and only two were published after 2015. Research reports emergy analysis in different scenarios: constructed wetlands (Arias and Brown, 2009;Chen et al, 2009;Siracusa and la Rosa, 2006;Zhou et al, 2009), municipal wastewater (Björklund et al, 2001;Ciobanu et al, 2022), organization system (Bastianoni and Marchettini, 1997) and specifically water treatment with microalgae (Grönlund et al, 2004).…”
Section: Documentsmentioning
confidence: 99%
“…This is what is really important to treat wastewater from different activities using technology. Furthermore, it is necessary to apply some environmental management instruments to quantify the activities of humans that cause direct and indirect effects on the environment, to enable decision-makers to track and measure progress towards sustainability goals and outcomes (Ciobanu et al, 2022). Some of these instruments could be Life Cycle Assessment (LCA) (Bonton et al, 2012;Raghuvanshi et al, 2017), water footprint (Huang et al, 2022;Johnson and Mehrvar, 2019;Romeiko, 2019), exergy analysis (Li et al, 2021) and emergy analysis (Ciobanu et al, 2022;Liu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there is a growing global interest in the reuse of wastewater as a strategy to ensure a consistent water supply for agriculture [23,24]. Many studies have been conducted to evaluate the effectiveness of this technique [25,26].…”
Section: Introductionmentioning
confidence: 99%